2020
DOI: 10.3390/su12083176
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High-Speed Rail Opening on City Economics along the Silk Road Economic Belt

Abstract: Achieving transport connectivity is a priority in China's "Belt and Road Initiative". In order to further understand the impact of railway infrastructure on city-level economic expansion, we set cities with high-speed rail as the treatment group and those without high-speed rail as the control group, and a difference-in-differences (DID) technique was used to estimate the growth impact and heterogeneity of high-speed rail opening on the economic growth of cities along the New Silk Road Economic Belt. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…The empirical analysis of the study identified that the HSR launch tends to influence economic growth significantly. Researchers have also investigated the influence of the HSR on economic growth, and it was identified that large cities tend to have a significant influence that increases economic growth significantly [35]. The findings of this study are supported by a study that also found that the opening of the HSR tends to impact economic growth significantly, and, in this way, the study findings are strongly supported [22].…”
Section: Hsr Along With Quality Of Place Improves Regional Economic Growthsupporting
confidence: 71%
See 2 more Smart Citations
“…The empirical analysis of the study identified that the HSR launch tends to influence economic growth significantly. Researchers have also investigated the influence of the HSR on economic growth, and it was identified that large cities tend to have a significant influence that increases economic growth significantly [35]. The findings of this study are supported by a study that also found that the opening of the HSR tends to impact economic growth significantly, and, in this way, the study findings are strongly supported [22].…”
Section: Hsr Along With Quality Of Place Improves Regional Economic Growthsupporting
confidence: 71%
“…High-speed railways may improve urban development conditions, enhance the connection between the city and a more comprehensive range of markets, industrial chains and increase the market for companies along the route. High-speed rail can promote the free flow of labor, attract corporate headquarters to gather along the highspeed rail, and promote the simultaneous development of regional economic integration and industrial agglomeration [35]. A detailed literature review on the agglomeration impact of transport investment concluded that public transport improvement could bring considerable external benefits by promoting an agglomeration economy [36].…”
Section: Impact Of Hsr On Urban Agglomerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Крупные города, подключенные к системе ВСМ, демонстрируют тенденцию к аккумулированию ресурсов из меньших городов, что усиливает их экономическое развитие. Однако, средние и небольшие города в большей степени чувствительны к изменению заработной платы, вызванной транспортной доступностью, нежели крупные [8].…”
Section: транспортная доступность как индикатор экономического развития территорийunclassified
“…These indicators often contain terms such as "mobility" [6], "efficient transportation", or "transportation and roads" [7]. When dealing with the sustainability of transportation and the efficient movement of people and goods, in addition to topics such as railways [8] and public transportation [9][10][11][12][13], the urban road network is a major research area [14][15][16][17][18][19][20]. This stems from the fact that road network performance (RNP) can lead to significant negative impacts on all three dimensions of urban sustainability.…”
Section: Introductionmentioning
confidence: 99%